Resolva as inequações
a) 2 (x - 4) - 3 (x + 8) > 3x
Anexos:
![](https://pt-static.z-dn.net/files/d35/c42365b1e809c5f2e823f6969099e48c.jpg)
Soluções para a tarefa
Respondido por
0
Resposta:
Explicação passo-a-passo:
a)
2.(x - 4) - 3 (x + 8) > 3x
2x - 8 - 3x - 24 > 3x
- x - 32 > 3x
- x - 3x > 32
- 4x > 32 (-1)
4x < - 32 (:4)
X < - 8
R.: {x E R / x < - 8}
_______
b)
1 - 2.(x - 1) < 2 - x
1 - 2x + 2 < 2 - x
1 - 2x < x + 2 - 2
1 - 2x < x
- 2x - x < - 1
- 3x< - 1 (-1)
3x > 1
x > 1/3
R.: {X E R / x > 1/3}
________
C)
1/2 - 4x ≤ 4x - 3/4
- 4x - 4x ≤ - 3/4 - 1/2
- 8x ≤ (-3 - 2)/4
- 8x ≤ - 5/4 (-1)
8x ≥ 5/4
32x ≥ 5
X ≥ 5/32
R : {x E R / x ≥ 5/32}
Perguntas interessantes
História,
7 meses atrás
Matemática,
7 meses atrás
Matemática,
9 meses atrás
História,
9 meses atrás
Ed. Física,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás